RESPONS BIBIT JARAK PAGAR PADA BERBAGAI KOMPOSISI MEDIA TANAM DAN KONSENTRASI PUPUK DAUN NOVELGRO - Ainun Marliah (Jurnal Floratek, 2010)
The ojectives of this research were to study effect of media composition and  foliar fertilizer of NOVELGRO concentration on growth Jatropha curcas.  Experimental design used was a factorial 3x4 with three replications. Factors investigated were growth media composition with a ratio of 1:1:1 (soil, compost, sand), (soil, compost, and rice husk), (soil, compost, saw dust), and Novelgro concentration of 0, 1, 2 and 3 cc/L of water.  Results showed that there was a significant effect of growth media composition on plant growth and leaf number  at  35, 45 and 55 day after planting (DAP), stem diameter at 45 and 55 DAP, fresh weight, dry weight and dry weight of root, but the media composition did not show significant  effect on plant growth and leaf number at 25 DAP and stem diameter at 25, 35 DAP. The best growth was found at media composition of soil, compost and sand with a ratio of 1:1:1.  Fertilizer concentration significantly affected stem diameter at 25 DAP but did not show a significant affect on plant growth and leaf number at 25, 35, 45, and 55 DAP, stem diameter at 35, 45, and 55 DAP, fresh weight, dry weight and dry weight of root. Plant growth was best at a fertilizer concentration of 2cc/L of water. There was no significant interaction between growth media composition and fertilizer concentration on all variables observed.